Pharmacogenetics of CYP1A2, Novel Polymorphisms and Haplotypes in Three Distinct Asian Populations - Lim, Joanne Siok Liu; Singh, Onkar; Ramasamy, Rathi Devi; Ramasamy, Saminathan; Subramanian, Koilan; Lee, Edmund J.D.; Chowbay, Balram (DRUG METABOLISM AND PHARMACOKINETICS, 2010)
CYP1A2 play an important role in the metabolism of many carcinogens and clinically important drugs. CYP1A2 activity has been found to be influenced by the presence of polymorphic variants which were reported to display wide interethnic variation. This study investigates the frequency distribution and linkage disequilibrium patterns of CYP1A2 genetic polymorphisms, and characterize their haplotype structures in three healthy Asian populations in Singapore (Chinese, Malay, and Indian). The entire CYP1A2 gene was screened in 126 healthy subjects from all three ethnic groups (N = 42 each). A total of 25 polymorphisms was identified, of which nine were novel. The polymorphisms, −2467delT and − 163C>A were detected at high frequencies in all Asian ethnic groups. Significant interethnic differences were observed in the genotypic frequency distribution of IVS2 – 99G>A (P<0.01) and 1548C>T (P = 0.05) across the three ethnic groups while – 163C > A (P = 0.02) was found to differ between Chinese and Malays. Haplotype analyses revealed four to six major haplotypes in each ethnic population which accounted for more than 60% of the cumulative haplotype frequencies. Future studies should be done to investigate the functional roles of these haplotypes.